Predictors of 1-year mortality in patients with contemporary guideline-adherent therapy after acute myocardial infarction: results from the OMEGA study - Liosis, Spyridon; Bauer, Timm; Schiele, Rudolf; Gohlke, Helmut; Gottwik, Martin; Katus, Hugo; Sabin, Georg; Zahn, Ralf; Schneider, Steffen; Rauch, Bernhard; Senges, Jochen; Zeymer, Uwe (Clinical research in cardiology, 2013)
Predictors of long-term mortality after discharge after acute myocardial infarction (AMI) are well characterized. However, these established risk factors are based on data almost exclusively derived from older studies without consistent use of revascularization therapy and adjunctive therapy with statins, platelet inhibitors, beta-blockers and ACE inhibitors/ARBs. We therefore sought to investigate predictors of 1-year mortality in survivors of AMI treated with contemporary guideline-adherent therapy.